2011
DOI: 10.1002/job.765
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual orientation harassment in the workplace: When do observers intervene?

Abstract: In Ryan and Wessel (2011), we presented the ordinary least square regression analyses in Tables 4, 5, 8, and 9 rather than the logistic regression analyses. Reanalysis of the data using logistic regression results in no changes in the conclusions regarding any of the hypotheses or any of the conclusions regarding significant relations for any of the variables. We presented herein parallel tables for comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 66 publications
2
37
1
Order By: Relevance
“…The nature of the harassment affects observer's likelihood of intervention (Bowes-Sperry & O'Leary-Kelly, 2005;Clark & Word, 1972;1974;Ryan & Wessel, 2012). Specifically, Bowes-Sperry and Powell (1999) found that observers were more likely to intervene when they perceived there was a consensus that an incident constituted sexual harassment than when there is a lack of confidence regarding what the incident actually represented.…”
Section: Situational Influencesmentioning
confidence: 99%
See 3 more Smart Citations
“…The nature of the harassment affects observer's likelihood of intervention (Bowes-Sperry & O'Leary-Kelly, 2005;Clark & Word, 1972;1974;Ryan & Wessel, 2012). Specifically, Bowes-Sperry and Powell (1999) found that observers were more likely to intervene when they perceived there was a consensus that an incident constituted sexual harassment than when there is a lack of confidence regarding what the incident actually represented.…”
Section: Situational Influencesmentioning
confidence: 99%
“…It is also one of the few observer intervention frameworks that focuses on workplace harassment incidents as opposed to emergency situations most often addressed in the bystander literature (e.g., Clark & Word, 1972). Although the Bowes-Sperry and O'Leary-Kelly's framework primarily focuses on sexual harassment, it has been shown to generalize to sexual orientation harassment (Ryan & Wessel, 2012), making it a suitable framework from which to develop hypotheses on observer intervention in religious harassment.…”
Section: Observer Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ryan and Wessel (), we presented the ordinary least square regression analyses in Tables 4, 5, 8, and 9 rather than the logistic regression analyses. Reanalysis of the data using logistic regression results in no changes in the conclusions regarding any of the hypotheses or any of the conclusions regarding significant relations for any of the variables.…”
Section: Logistic Regression Of Intervention On Hypothesized Variablementioning
confidence: 99%